Applying the Taguchi Method to Optimise the Size of Silica Nanoparticles Entrapped with Rifampicin for a Drug Delivery System - Zainal, Nor Ain; Shukor, Syamsul Rizal Abd.; Razak, Khairunisak Abdul (Taylor's University, 2015)
The aim of this study was to optimise the experimental conditions for the synthesis of silica nanoparticles. In achieving this, the amount of butanol, the amount of surfactant, the amount of silica precursor, the synthesis temperature and the agitation speed were optimised by applying the Taguchi orthogonal arrays method. The optimal synthesis conditions for silica nanoparticle production were a temperature of 50°C, 6 ml butanol, 7 ml Tween 80, 3 ml trimethoxyvinylsilane (TMVS), and an agitation speed of 320 rpm. The nanoparticle size was characterised to optimise the synthesis conditions and determined to be smaller than 100 nm using a Malvern Zetasizer Nano ZS and a transmission electron microscope (TEM).